PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI KABUPATEN MUSI BANYUASIN - Ruslan, Ruslan (Jurnal Ilmu Manajemen, 2012)
This study aimed to investigate the effect of the work environment (X1), motivation (X2) and Leadership (X3) on Employee Performance Agency for Family Planning and Women Empowerment Musi Banyuasin, either jointly or partially. Taken together with the results obtained Fhitung F test of 42.178 is greater than the F table 2.883, significant F value of 0.000 which is less than ? (0.05), with the results explained that the work environment (X1), Motivation ( X2) and Leadership (X3) significantly affect the performance (Y). In the t-test with variable motivation (X2) thitung results obtained by 1.957 which is smaller than the TTable 2.032, significant value of 0.060 t greater than the value of ? (0.05), with the result explains that motivation (X2) does not affect to Performance (Y). In the Work Environment variable (X1) and Leadership (X3) obtained thitung results obtained for 2.118 and 4.545 greater than 2.032 ttabel, significant values of 0.043 and 0.041 t smaller than the value of ? (0.05), with the result explained that the Working Environment (X1) and Leadership (X3) partially significant effect on performance (Y). Through determination test in the study found that the performance of (Y) can be explained by work environment (X1), motivation (X2), and the leadership (X3) has amounted to 80.8%, while the remaining 19.2% is explained by other factors not included in this study.